Hidden hunger? Experiences of food insecurity amongst Pakistani and white British women. Issue 11 (8th October 2018) - Power, Maddy; Small, Neil; Doherty, Bob; Pickett, Kate E.
Abstract : Purpose: Foodbank use in the UK is rising but, despite high levels of poverty, Pakistani women are less likely to use food banks than white British women. The purpose of this paper is to understand the lived experience of food in the context of poverty amongst Pakistani and white British women in Bradford, including perspectives on food aid. Design/methodology/approach: A total of 16 Pakistani and white British women, recruited through community initiatives, participated in three focus groups (one interview was also held as a consequence of recruitment difficulties). Each group met for two hours aided by a moderator and professional interpreter. The transcripts were analysed thematically using a three-stage process. Findings: Women in low-income households employed dual strategies to reconcile caring responsibilities and financial obligations: the first sought to make ends meet within household income; the second looked to outside sources of support. There was a reported near absence of food insecurity amongst Pakistani women which could be attributed to support from social/familial networks, resource management within the household, and cultural and religious frameworks. A minority of participants and no Pakistani respondents accessed charitable food aid. There were three reasons for the non-use of food aid: it was not required because of resource management strategies within the household and assistance from familial/social networks; it was avoided out of shame; and knowledge about its existence was poor. Originality/value: This case study is the first examination of varying experiences of food insecurity amongst UK white British and Pakistani women. Whilst the sample size is small, it presents new evidence on perceptions of food insecurity amongst Pakistani households and on why households of varying ethnicities do not use food aid.